Genomic analysis of acid tolerance genes and deciphering the function of ydaG gene in mitigating acid tolerance in Priestia megaterium - Darshana Sharma; Purna Bahadur Chetri; Vipin Ranga; Subhajit Sen; Bidyut Kumar Sarmah; Bidyut Kumar Sarmah; Madhumita Barooah; Madhumita Barooah (Frontiers in Microbiology, 2024)
Adverse environmental conditions, such as acid stress, induce bacteria to employ several strategies to overcome these stressors. These strategies include forming biofilms and activating specific molecular pathways, such as the general stress response (GSR). The genome of Priestia megaterium strain G18 was sequenced using the Illumina NextSeq 500 system, resulting in a de novo assembly of 80 scaffolds. The scaffolded genome comprises 5,367,956 bp with a GC content of 37.89%, and was compared to related strains using the MiGA web server, revealing high similarity to P. megaterium NBRC 15308 and P. aryabhattai B8W22 with ANI scores of 95.4%. Phylogenetic and ribosomal multilocus sequence typing (rMLST) analyses, based on the 16S rRNA and ribosomal protein-encoding alleles, confirmed close relationships within the P. megaterium species. Functional annotation identified 5,484 protein-coding genes, with 72.31% classified into 22 COG categories, highlighting roles in amino acid transport, transcription, carbohydrate metabolism, and ribosomal structure. An in-depth genome analysis of P. megaterium G18 revealed several key genes associated with acid tolerance. Targeted inactivation of the ydaG gene from SigB regulon, a general stress response gene, significantly reduced growth under acidic conditions compared to the wild type. qRT-PCR analysis showed increased ydaG expression in acidic conditions, further supporting its role in acid stress response. Microscopic analysis revealed no morphological differences between wild-type and mutant cells, suggesting that ydaG is not involved in maintaining cellular morphology but in facilitating acid tolerance through stress protein production. This research contributes to understanding the molecular mechanisms underlying acid tolerance in soil bacteria, P. megaterium, shedding light on potential applications in agriculture and industry.